Assessing business sustainability for a small business venture using SWOT analysis - Othman, Abdul Kadir; Noranee, Shereen; A Rahman, Mohd Khirzanbadzli; Rochin Demong, Nur Atiqah (Universiti Teknologi Mara Selangor, 2024)
A highly competitive business environment demands a company to have specific, unique characteristics. A company must have a good management structure and system, exceptional products, integrated marketing, strong financial standing, and visionary leadership. A newly created start-up struggles to establish itself and compete with more developed companies, making it susceptible to threats and challenges in the market. Using the interview data and observation, this paper aims to investigate factors that facilitate the business growth of a new venture and those that hinder its development. The findings are tabulated in the SWOT analysis table for better understanding. The results indicate that, for a new business venture, the entrepreneur or the owner plays a significant role in paving the way for the company’s future growth. The entrepreneur must be bold enough to make risky decisions to put the company on the right track for business sustainability.